Strategi Guru dalam Membentuk Karakter Islami Anak Usia Dini di TK IT Rabbani Muara Enim - Winsidi Winsidi; Akmal Ramdhan (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze teachers’ efforts in instilling Islamic character values in early childhood at TK IT Rabbani Muara Enim, as well as to identify supporting and inhibiting factors. This research used a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving teachers and the principal. The results show that teachers instill Islamic values through habituation, including greeting, handshaking, memorizing daily prayers, practicing prayer, and fostering discipline and independence. The implementation is carried out through routine, integrated, and special programs. Supporting factors include collaboration between teachers and parents, adequate facilities, and students’ internal motivation. Inhibiting factors include lack of family supervision, diverse student characteristics, and limited concentration during learning. Overall, consistent habituation and cooperation among school and family play an important role in developing Islamic character in early childhood.